PENINGKATAN PENGETAHUAN MASYARAKAT MENGENAI PERKEMBANGAN DAN PENYEBARAN DBD - Tri Puji Lestari Sudarwati; M.A Hanny Ferry Fernanda; Mercyska Suryandari (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2021)
This community service event was aimed to elevate the knowledge of local society regarding the current update of Aedes aegypti mosquito as a vector of Dengue Hemorrhagic Fever (DHF). Hence, it raised awareness of their role in breaking the disease transmission. Involving students as supporting team, this activity was carried out at Jemur Gayungan RW 01 by giving public counselling and mentoring for the larvae surveyor cadre (Jumantik). Abdimas, which has been done, adds to the knowledge of jumantik cadres about the proliferation and spread of dengue, so that jumantik cadres not only observe their environment but can also take action to break the chain of dengue spread.